2004
DOI: 10.1148/radiol.2332031802
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Electrophysiologic Monitoring after Injection of Gadobenate Dimeglumine versus Placebo in Healthy Volunteers and Patients with Cardiovascular Disease

Abstract: Injection of 0.2 mmol/kg gadobenate dimeglumine has no detrimental effect on cardiac electrophysiology or other safety parameters in healthy volunteers or patients with CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Moreover, cardiodepressive and hypotensive effects caused by gadopentetate dimeglumine are dose-dependent [ 24 , 26 ]. This data was confirmed by Pirovano et al who showed that the injection of 0.2 mmol/kg gadobenate dimeglumine had no detrimental effect on cardiac electrophysiology, or other safety parameters, in healthy volunteers or patients with coronary artery disease [ 27 ].…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, cardiodepressive and hypotensive effects caused by gadopentetate dimeglumine are dose-dependent [ 24 , 26 ]. This data was confirmed by Pirovano et al who showed that the injection of 0.2 mmol/kg gadobenate dimeglumine had no detrimental effect on cardiac electrophysiology, or other safety parameters, in healthy volunteers or patients with coronary artery disease [ 27 ].…”
Section: Discussionsupporting
confidence: 56%
“…To date, more than 4000 subjects have been administered Gd‐BOPTA in clinical trials, while a further 1.5 million patients have been administered the agent in routine clinical practice (Bracco Diagnostics, Inc., data on file). Reports published to date on the safety of Gd‐BOPTA in clinical trials and on the basis of postmarketing surveillance have shown that this agent is well‐tolerated by patients and that the incidence and type of reported AE are similar to those reported for other approved gadolinium agents (22–24). Literature comparisons of the safety profiles of Gd‐BOPTA and other FDA‐approved gadolinium agents have confirmed that the differences between these agents are negligible, particularly with regard to the most frequently reported AE (Table 5) (18, 24–28).…”
Section: Discussionmentioning
confidence: 71%
“…A randomized, double‐blind, placebo‐controlled, crossover clinical trial in patients requiring contrast‐enhanced MRI did not show any significant QTc prolongation with gadoterate meglumine 22 . In a 2‐way crossover study comparing gadobenate at a dose of 0.2 mmol kg −1 to placebo an increase of 3.1 ms in ΔΔQTcB was observed with no difference between healthy volunteers and patients with coronary artery disease 23 . It is interesting to note that both gadobutrol and gadobenate have a higher osmolarity at marketed concentrations (1603 and 1970 mOsm l −1 , respectively) than gadopiclenol (843 mOsm l −1 ) 13 .…”
Section: Discussionmentioning
confidence: 90%